Effect of Papaya Leaf Extract (Carica papaya L.) on Colony Diameter and Percentage of Growth Inhibition of Fusarium oxysporum - Meriza Fatma; Moralita Chatri; Mades Fifendy; Dezi Handayani (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2021)
This study aimed to determine the effect of leaf extract concentration of C. papaya on the diameter of colonies F. oxysporum and the percentage of inhibition of growth of F. oxysporum. This research was conducted from February to April 2021 at the Integrated Research Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This study was an experimental study consisting of 5 treatments and 3 replications with the administration ofleaf extract at a C. papaya concentration of 0% (control), 10%, 20%, 30% and 40%. The data obtained were analyzed by means of variance (ANOVA) with Duncan's New Multiple Range Test (further testDNMRT)and the percentage of inhibition was analyzed descriptively. The results showed that leaf extract C. papaya at concentrations of 20%, 30% and 40% significantly affected the diameter of thecolonies F. oxysporum. The smallest colony diameter was at a concentration of 40% was 5.35 cm and the largest colony at a concentration of 10% was 6.61 cm. While the smallest percentage of inhibition at a concentration of 10% was 5% and the largest percentage of inhibition is at a concentration of 40% was 23%.